An ultrasonographic study of knee joints: features of inflammation and their relationship to radiographic osteoarthritis and pain - Hall, Michelle C. (2013)
Background. Knee osteoarthritis (OA) can result in considerable pain and disability for some people. Inflammation within the joint may be partly responsible for the pain associated with OA and a link between inflammation and disease progression has been suggested. Ultrasound (US) imaging has been successfully employed in the evaluation of knee joint effusion, synovial hypertrophy and power doppler signal (PDS) which are said to represent joint inflammation. The associations between US features of inflammation, knee pain and radiographic OA have yet to be firmly established.